2016
DOI: 10.1128/jvi.02502-15
|View full text |Cite
|
Sign up to set email alerts
|

Parainfluenza Virus 3 Blocks Antiviral Mediators Downstream of the Interferon Lambda Receptor by Modulating Stat1 Phosphorylation

Abstract: Parainfluenza viruses are known to inhibit type I interferon (IFN) production; however, there is a lack of information regarding the type III IFN response during infection. Type III IFNs signal through a unique heterodimeric receptor, IFN-R1/interleukin-10R2 (IL-10R2), which is primarily expressed by epithelial cells. Parainfluenza virus 3 (PIV-3) infection is highly restricted to the airway epithelium. We therefore sought to examine type III IFN signaling pathways during PIV-3 infection of epithelial cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Our study demonstrated that PIV3 and RV1B induce IFN-k1 generation both at the protein and mRNA levels in human nasal epithelial cells. This observation is in line with earlier studies documenting that PIV3 induces a type III IFN response in the epithelial cells, although it may interfere with downstream anti-viral signalling pathways [38]. Type I IFN (IFN-b) was detected only at mRNA level after infection with both RV1B and PIV3.…”
Section: Discussionsupporting
confidence: 91%
“…Our study demonstrated that PIV3 and RV1B induce IFN-k1 generation both at the protein and mRNA levels in human nasal epithelial cells. This observation is in line with earlier studies documenting that PIV3 induces a type III IFN response in the epithelial cells, although it may interfere with downstream anti-viral signalling pathways [38]. Type I IFN (IFN-b) was detected only at mRNA level after infection with both RV1B and PIV3.…”
Section: Discussionsupporting
confidence: 91%
“…Only a few studies have explored this in the context of IFN-位s. Parainfluenza virus 3 blocks antiviral mediators downstream of the IFNLR signaling by modulation of the STAT1 phosphorylation in BEAS 2B cells, a bronchial epithelial cell line (144). Dengue virus was recently shown to induce IFNL1 via its non-structural protein (NS1) in order to facilitate dendritic cell migration (114).…”
Section: Viral Infectionsmentioning
confidence: 99%
“…15 BHV, and many other viruses of the BRD complex, including BVDV, BRSV, and PIV, however, have mechanisms in place to actively suppress the host IFN response. [16][17][18][19] In 1 report, coinfection of bovine epithelial cells with BVDV inhibited type I IFN production, enabling significantly increased replication of BRSV in the same cell cultures, 19 suggesting a synergistic interaction between the 2 viruses.…”
Section: Airway and Lung Epithelia And Resistance To Bovine Respiratomentioning
confidence: 95%